An injury audit in high-level male youth soccer players from English, Spanish, Uruguayan and Brazilian academies - Hall, E. C. R.; Larruskain, J.; Gil, S. M.; Lekue, J. A.; Baumert, P.; Rienzi, E.; Moreno, S.; Tannure, M.; Murtagh, C. F.; Ade, J. D.; Squires, P.; Orme, P.; et al. (Physical Therapy in Sport, 2020)
Objectives: To identify the most common injury types/locations in high-level male youth soccer players (YSP). Design: Prospective cohort surveillance study. Setting: Professional soccer club academies. Participants: Six hundred and twenty-four high-level male YSP [Under 9 (U9) to U23 year-old age groups] from academies in England, Spain, Uruguay and Brazil. Main outcome measures: Injury type, location and severity were recorded during one season. Injury severity was compared between age groups, while injury type and location were compared between nations. Results: Four hundred and forty-three training or match injuries were recorded, giving an injury rate of 0.71 per player. Non-contact injuries were most common (58.5%), with most (44.2%) resolved between 8 and 28 days. Most injuries (75.4%) occurred in the lower limbs, with muscle (29.6%) the most commonly injured tissue. U14 and U16 suffered a greater number of severe injuries relative to U12 and U19/U20/U23/Reserves. Tendon injury rate was higher in Brazil vs. Spain (p < 0.05), with low back/sacrum/pelvis injury rate highest in Spain (p < 0.05). Conclusions: The proportion of severe injuries in U14 and U16 suggests YSP injury risk is maturation-dependent. Minimal differences in type and location between high-level YSP from four different countries suggest injury rates in this population are geographically similar.